The family Hydropsychidae Curtis (Trichoptera) in the Ryukyu Archipelago, southwestern Japan - Ito, Tomiko; Nozaki, Takao (Zootaxa, 2018)
The caddisfly family Hydropsychidae Curtis is revised for the Ryukyu Archipelago, southwestern Japan. Four new species are described based on adults: Diplectrona uken Ito and Nozaki sp. nov., Homoplectra crassicornea Nozaki and Ito sp. nov., Homoplectra trifurcata Nozaki and Ito sp. nov. and Cheumatopsyche aira Ito and Nozaki sp. nov. Based on examination of type specimens of species described from Taiwan in 1910–1930’s: Cheumatopsyche uchidai Kobayashi 1987 and Hydropsyche yaeyamensis Tanida 1986 are synonymized with C. clavalis Martynov 1930 and H. orbiculata Ulmer 1911, respectively. Five East Asian species: Diplectrona burha Schmid 1961, Diplectrona albofasciata (Ulmer 1913), Cheumatopsyche clavalis Martynov 1930, Hydropsyche verrucosa (Ulmer 1911), and Macrostemum formosicolum (Matsumura 1931) are recorded from Japan for the first time and re-described. Adults of two known species, Cheumatopsyche okinawa Oláh and Johanson 2008 and Macrostemum okinawanum (Matsumura 1931) are re-described. Females of five species, previously known only as males, are described for the first time.